RING WORM INFECTION IN A GOAT - A CLINICAL CASE REPORT - G. Kalaiselvi,; N. Daniel Joy Chandran,; M. Vidhya, (Indian Journal of Veterinary and Animal Sciences Research, 2024)
A 3 months old goat kid presented to Veterinary Dispensary, Chetiyur, Salem district Tamil Nadu   with case history of ring like patches on the body complete alopecia, frequent itching with thick and scaly skin . Dermatophytes are cited among the most frequent causes of dermatological problems in domestic animals. The superficial mycoses caused by dermatophytes are called dermatophytosis- Trichophyton are usually the cause of dermatophytosis in domestic animals. Trichophyton verrucosum is the major fungal agent encountered in case of goats. Direct microscopic examination of skin scrapping with 20% KOH revealed long chains densely packed chlamydiospore found with swollen hyphae. The skin scrapping materials cultured in thiamine inositol nutrient supplement selective culture medium. Long chains of densely compacted chlamydospores present in lactophenol cotton blue staining. The goat kid recovered within a week by external antifungal and systemic antibiotic and nutritional therapy with good hygienic management.